Drawing as a Way of Knowing: Visual Practices as the Route to Becoming Academic - Abegglen, Sandra; Burns, Tom; Sinfield, Sandra (Discourse and Writing/Rédactologie, 2018)
This case study illustrates what happened when we took a playful approach in a first year undergraduate academic skills module and a graduate Facilitating Student Learning module asking our students to “draw to learn.” We found that they not only enjoyed the challenges we set them, but also that they “blossomed” and approached their academic writing with more confidence and joy. Hence we argue for a more ludic approach to learning and teaching in Higher Education to enable Widening Participation students and their tutors to become the academic writers they want to be. In particular “blind drawing” seems to be a powerful tool for diminishing the fear of failure and for fostering deep understanding as well as self-confidence.